School-work-transition of NEETS: a comparative analysis of European countries - Rocca, Antonella; Neagu, Gabriela; Tosun, Jale (Youth & society, 2022)
This study investigates the connection between the reasons why some young people end their education without attaining a university degree and the effect of this decision on the probability of becoming a NEET in a set of European countries. Young people face the highest degree of disadvantage in the Mediterranean and East European countries, whereas in Continental European countries the school-to-work transition is smooth. We use the ad hoc module of the 2016 Labour Force Survey (LFS) and focus on young people aged 15 to 24. Our analysis reveals a positive relationship between the decision to drop out of education for health or family reasons and the probability of becoming a NEET. Conversely, when the reason for not completing university education is the desire to start working, and when the individuals who dropped out of university education gathered work experience during this period, the probability of becoming a NEET decreases significantly.